Household cooking frequency and diet quality are mediated by food shopping behaviors among U.S. African-American adults: A NHANES analysis. - Nicole Farmer; Narjis Kazmi; Kristina Franklin; Li Yang; Tiffany M Powell-Wiley; Gwenyth R Wallen (PLoS ONE)
Among U.S. adults who self-identified as African-American, frequent household cooking is related to better dietary quality and adherence to U.S. dietary guidelines, as measured by the Healthy Eating Index. However, African-Americans often reside in commercially disinvested areas with limited access to major food retailers. This study examined whether food shopping behaviors-travel time to grocery store and frequency of major food shopping-affect the relationship between cooking frequency and diet quality, potentially influencing community nutrition education outcomes. Using data from 2,434 non-Hispanic Black adults (≥ 18 years) from the 2007-2010 NHANES cycles, we performed linear regression analysis with Complex Sample General Linear Models (CSGLM). The Healthy Eating Index 2010 measured daily and dinner dietary quality. Mediation analysis was conducted to evaluate if food shopping behaviors are involved in potential causal pathways. Results showed that major food shopping frequency, but not travel time to a grocery store, was significantly associated with daily diet quality and cooking frequency (p < 0.001). Mediation analysis revealed that food shopping frequency significantly mediated the relationship between cooking frequency and dinner quality (52.44% mediating effect). When stratified by food security status, shopping frequency was only a significant mediator of cooking frequency and diet quality for those with full or marginal food security (64.89% mediating effect). For food-insecure individuals, major food shopping did not mediate the cooking-diet quality relationship. These findings suggest that food shopping frequency is a critical factor when assessing the link between cooking frequency and diet quality, and may inform factors to optimize food shopping behaviors within community nutrition education programs among those experiencing food-insecurity in the U.S.